Globalisation in Africa: Examining if Economic Integration and Privatisation of Most Public Enterprises in West Africa Instigates Migration Crisis in the ECOWAS Sub-region - Nwawube, Arinze Victor; Ezugworie, Chikwado Collins; Ugwu, Leonard Ifeanyi Jr.; Onwunyiri, Ndubuisi Ebuka (Journal of Contemporary International Relations and Diplomacy, 2024)
This study broadly examined if globalisation instigated migration crisis in the West African sub-region. Specifically, the study investigated the role of economic integration in the rise of migration and the positive link between privatisation and increased movement in West Africa. The Growth Pole theory was adopted to explain the interconnection between globalisation and migration. The study employed the documentary method of data collection and the qualitative descriptive method of data analysis otherwise known as content analysis. The study found that the paucity of implementation of economic integration schemes adopted in the West African sub-region has led to the rising trend of various forms of migration, ranging from irregular migration, forced migration, labour migration etc. It also found that privatisation measures in West Africa have been implicated in the increased movement of people across the sub-region, especially intra-regional movement, from rural to the urban area. Consequently, the study recommended that since rising trend of various forms of migration within the West African sub-region is traceable to the paucity in the enforcement of the economic integration schemes adopted in the sub-region, the Economic Community of West African States (ECOWAS), among others, therefore, should strengthen enforcement structures, collaborate with member states, and establish an ECOWAS Cross-border Cooperation Fund.